Evaluation of the operation Big Brother Program in selected public schools in the Division of City Schools Manila - Intatano, Vivian Batol (2008)
This study aimed to evaluate the Operation Big Brother (OBB) Program that was implemented in the 3 selected public schools in the Division of City Schools, Manila. It is conducted through a descriptive method of research. Questionnaire was the main instrument used. The major findings of the study include: 1. The important feature of the OBB Program is the enhanced curriculum implemented in selected schools; and 2. Teacher trainings, benefits to the students and learning materials are the components which are geared towards the successful implementation of the program. The findings confirmed that the administrators, teachers, and parents perceived the program as successful in meeting its objectives. Respondents believed that the objective to give quality education was achieved.
Vita.
"April 2008."
Thesis (M.A. Eudcational Administration)--University of the Philippines Diliman.
Keywords: Public schools -- Philippines -- Manila -- Administration; Curriculum planning -- Philippines -- Manila